The adaptable longboard - Basil Ryan Bin Shariman (Nanyang Technological University, 2023)
The Adaptable Longboard project aims to reinvent the way we perceive the use of longboards and also integrate a more sustainable approach towards the way we interact with them by introducing multi-purpose and multi-functional features. By taking into consideration the target audiences preference for a multi-purpose and multi-functional Longboard, it only seemed appropriate to incorporate an intuitive way of expanding and collapsing the board that would enable the flexibility of use. Such adaptability would also tend to allow for a user-friendly board that caters to all skill levels. In addition, the project’s approach of altering the way we perceive the life cycle of a Longboard from a replaceable piece to a long-term companion that adapts to the user, promotes the idea of being more environmentally conscious with our skating habits.